2019
DOI: 10.1186/s41935-019-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and anesthetic deaths: toxicological and medico legal aspects

Abstract: Background: Anesthesia has become safer during decades, though there is still a preventable mortality; the complexity of medical and surgical interventions, increasingly older and sicker patients, has created a host of new hazards in anesthesiology. In this paper, some of these perioperative (PO) fatal adverse events are investigated in terms of health responsibility. Selective literature research in several data bases, concerning perioperative and anesthetic deaths and medical responsibility, was performed. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
(86 reference statements)
1
4
0
Order By: Relevance
“…This finding is consistent with the report of Li et al and Pascal et al [1,11]. However, Argo et al found more anesthetic deaths in females [12]. The reason for the gender differences in anesthetic deaths is not known.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is consistent with the report of Li et al and Pascal et al [1,11]. However, Argo et al found more anesthetic deaths in females [12]. The reason for the gender differences in anesthetic deaths is not known.…”
Section: Discussionsupporting
confidence: 91%
“…About half of the anesthesia-related mortality in the index study occurred in neonates. Disma et al also reported more mortality in neonates [12]. The reason for this may be because the fragile homeostasis of the neonate is adversely affected by the stress of surgery and anesthesia [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Associated sicknesses (e.g., pneumonic or renal) along with additional restriction in benchmark work and a modified neurohumoral reaction to push.  Increased occurrence of sudden responses to drugs, sedation and medical procedure [10].…”
Section: Three Elements Add To Expanded Danger In Older Patientsmentioning
confidence: 99%